Şanlıurfa Kültürü'nün Kadın Ve Erkek Giyim-kuşamına Etkisi - Karakeçili,Fethi (Sosyal Bilimler Enstitüsü, 1997)
Şanlıurfa kültürünün kadın ve erkek giyim-kuşamına etkisini konu alan bu tez, Şanlıurfa merkezi ile ilçe ve köylerinde yapılan çalışmalar, kaynak taraması ve görüşme metodu ile sonuçlanmıştır. Birinci bölümde; konuya genel bir giriş yapılmış ve yapılan çalışmalar.yaşanılan problemler anlatılmıştır. İkinci bölümde; Şanlıurfa ilinin tarihi, coğrafyası, tarihsel kronolojisi, ilçelerinin tarihi ve sosyal yapısı incelenmiştir. Üçüncü bölümde; Şanlıurfa civarında yaşayan toplulukların kültürel etkileşimleri ve giyim-kuşam'a etkisi üzerinde saptamalar yapılmıştır. Dördüncü bölümde; Şanlıurfa civarındaki ve dışındaki toplulukların kültürel etkileşimleri tartışılmıştır. Beşinci bölümde; Şanlıurfa folklorunun tarihçesi ve günümüze kadar yapılan derleme çlışmaları hakkında genel bilgilere yer verilmiştir. Altıncı bölümde; Giyim-kuşama genel bakışla açılımı yapılmış, etkenleri ve sonuçlan tartışılmıştır. Yedinci bölümde; Şanlıurfa da geçmişten günümüze giyim-kuşam üzerine saptamalar yapılmış, etkenleri ve sonuçları tespit edilmiştir. Sekizinci bölümde; Şanlıurfa yöresinde günümüz giyim-kuşamının tasnifi ve analizi yapılmıştır. Yörede yapılan derleme ve inceleme çalışması, sonuç ve bulgularıyla, yörede çekilen resimlerle anlatılmaya çalışılmıştır.

From past untill today, Şanlıurfa has been a culture bridge between many civilisations and protected thousands of cultural elements untill today, By reoson of it's position, Şanlıurfa is the centre of Mezzopotamia, Ancicent Greece and Anatolian culture, It's social structure lasts with tribe and land owners system, in an other word lasts with feudalism, and for this reason men and women clothers are rather various. In the first part, this thesis which takes "the effects of Şanlıurfa culture to men and women clothers" as a subject, not only contains the centre of Şanlıurfa but also the villages called Siverek, Harran, Akçakale, Hilvan, Viranşehir, Suruç and Bozova. Moreover the aim, importance and the borders of the study has expalined. In the second part, the necessory information from various sourced about the history of Şanlıurfa has explained with it's historicol chronology. The geographical location of the city has stated and ascertained the effects of the neighbor cities and countries. The history, social, cultyrel and ethnic structure of the villages has explained after examining the necessary sources. In the third part, the culture! influences between communities in Şanlıurfa and it's villages has explained. In addition the effects of these communitres to men and women clothes. ' These communities has bordered as Turkmens, Arabians, Kurds, Jewishes, Armenians and the others. In the fourth part, the cultural effects and influences of the communities out of Şanlıurfa has analized with reason-result connection. Also the connections between the arrangement of Şanlıurfa's folklore which has a rooted past, has given. Moreover studies of gathering took part in this section and has tried to have some results. The usefulness in today of these studies which have made by amateur and professional people, has discussed. In the sixth part, clothing has described with a large explanation. The attached elements which effect the clothing has explained; Defense instinct. Conform to nature conditions." The religious or philosophic beliefs. Appropriateness to their works. XI Administrative reforms. Economic conditions. Psychological tendency. The connection between those elements and the adaptation technigue to today has explainned. But the details about clothing are in the other parts. In the seventh part, men and women clothing has examined in Şanlıurfa from past untill today. In this part clothing especially in 18. and 19. centuries has explained with pictures and from archives documents. Because the only documents about 18. and 19. centuries cansist of the family albums of some special people. Also in this part, these three elements have discussed: 1- The effects of climate to clothing. 2- The effects of geographical conditions to clothing. 3- The effects of clothing between different communitres. Clothing in different professions has explained with samples and pictures as possible as could be. In the eighth part, men and women clothing analysis and classification has done in centre and sides of Şanlıurfa: Xll 1- Men's clothes wearing on;. Head.. Body. Waist. Under waist. Foot The similarity and difference between the clothes has tried to ascertain. 2- Women's clothes wearing on;. Head. Body. Waist. Under waist Foot xm The similarity and difference between the clothes has tried to ascertain. In addition the differences between young, old and married women clothes has explained village by village. The jewelery and accessory which take big place in clothing and the complementary elements of this part has explained with pictured samples. In addition the natural and otantic make-up has explained which is using by men and women in Şanlıurfa.
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 1997
Thesis (M.A.) -- İstanbul Technical University, Institute of Social Sciences, 1997
Keywords: Halk Bilimi (Folklor); Erkek giysileri; Giysiler; Kadın giysileri; Şanlıurfa; Folklore; Man clothes; Clothes; Woman clothing; Şanlıurfa